Taurine Alleviates Intestinal Injury by Mediating Tight Junction Barriers in Diquat-Challenged Piglet Models - Wen, Chaoyue; Guo, Qiuping; Wang, Wenlong; Duan, Yehui; Zhang, Lingyu; Li, Jianzhong; He, Shanping; Chen, Wen; Li, Fengna (Frontiers in Physiology, 2020)
Background: Intestinal barrier contributes as an important role in maintaining intestinal homeostasis. Oxidative stress can cause critical damages in intestinal integrity of animals. Objectives: This study was conducted to investigate the alleviated effect of taurine against small intestine (duodenum, jejunum, ileum) injury induced by oxidative stress. Methods: The piglet model of diquat-induced oxidative stress was employed. In addition, analysis of intestinal morphology, reverse transcription PCR (RT-PCR), and Western blot were used in this study. Results: Compared with the control group (CON), diquat-induced oxidative stress triggers immune response; the content of immunoglobulin M (IgM) and immunoglobulin G (IgG) was significantly changed, but 0.60% taurine supplementation could restore the level of serum immunoglobulin. Oxidative stress induces serious damage in intestinal morphology structure and tight junction barrier. Compared with the CON, the villus height of intestine was significantly decreased, the crypt depth and villus height/crypt depth (V/C) were also decreased, and 0.60% taurine supplementation could restore impaired morphology and even improve crypt depth and V/C of the jejunum and ileum. Compared with the CON, oxidative stress markedly increased the messenger RNA (mRNA) expression level of claudin-1 and occludin in the duodenum, and the value of occludin was significantly decreased in the jejunum of the diquat group (DIQ). Relative to the DIQ, 0.60% taurine supplementation increased the mRNA expression level of claudin-1, occludin, and ZO-1 in the ileum. Compared with the CON, the expression of claudin-1 protein was significantly upregulated, and occludin and ZO-1 protein were both downregulated in the small intestine of DIQ. Conclusion: Taurine exerts protective effects by regulating immune response and restores the intestinal tight junction barrier when piglets suffer from oxidative stress.